Eksternalitas Relokasi Pedagang Kaki Lima di Pasar Kuliner Kota Padang Panjang - Dimas Dwiyana Putra; Siska Sasmita (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2022)
A relocation that was managed by Padang Panjang Municipal Government for culinary market vendors has presented impacts for both the vendors and society. This study examines externality aspect that occurs after the relocation by using a descriptive qualitative approach. Data are obtained through interviews with stakeholders whose either taking role and affected by the relocation, namely: Local Trade Office of Small and Medium Business Cooperatives of Padang Panjang Municipal; the vendors; visitors of the culinary market; and parking attendants. The research findings are majority in line with dimensions of Coase’s Theorems: income distribution, negotiation, and solution. The vendors in the culinary market are becoming the most affected party of the relocation. Although they acquire positive externality by an increased income generating; the vendors also cannot avoid negative externalities that arise from social interaction to fellow vendors and a community around the culinary market.